Integrasi Smartphone dan ImageJ sebagai Inovasi Digital untuk Praktikum Deteksi Pencemaran Air di SMAN 13 Jambi - Martina Asti Rahayu; Dina Erliana; Indra Lasmana Tarigan; Dhian Eka Wijaya; Edwin Permana; Ayu Nadila Safitri (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Limited laboratory facilities have become a major obstacle in conducting science practicums at SMA Negeri 13 Jambi. In fact, laboratory activities are essential components of science education to develop students’ scientific skills and contextual conceptual understanding. This community service program aimed to enhance the capacity of teachers and students in conducting simple digital-based practicums using Smartphone Digital Image Colorimetry (SDIC) and the ImageJ software as an alternative to conventional spectrophotometry. The program employed a participatory and quasi-experimental approach through five main stages: (1) preparation and coordination with the school, (2) training on water pollution concepts and digital colorimetry principles, (3) demonstration of Fe²⁺ detection in environmental water samples using 1,10-phenanthroline, (4) color image analysis using ImageJ, and (5) evaluation of participants’ understanding and satisfaction. The subjects consisted of 25 eleventh-grade science students and 4 accompanying teachers selected purposively. Evaluation was conducted through pre- and post-tests, observation of practical skills, and satisfaction questionnaires. The results showed an average increase of 42.5% in students’ understanding after participating in the training, with a significant improvement in their ability to analyze color data. Additionally, 92% of participants stated that the SDIC method was engaging, easy to apply, and increased their interest in science practicums. The program produced printed and digital practical modules, ImageJ tutorial videos, and a contextual learning model that can be replicated in other schools with limited facilities. Therefore, the application of SDIC proved effective as an innovative, low-cost, and practical science learning approach that supports the strengthening of digital science literacy in secondary schools.